Designing model imino bifunctional chelators for radiopharmaceuticals – in vitro antitumor activity, photoluminescence and structural analysis. (8th March 2018) - Brink, Alice; Kroon, Robin E.; Visser, Hendrik G.; van Rensburg, Constance E. J.; Roodt, Andreas
Abstract : Designed bifunctional chelators for the radionuclides of 188/186 Re or 99m Tc. Structure, DFT calculations, antitumor and imaging properties are described. Abstract : Five imino salicylidene based bifunctional chelators were developed in order to act as a multipurpose ligand system. The chelators, namely 5-methyl-2-(1, 2, 4-triazol-3-yliminomethyl)phenol, 2-(9-ethylcarbazol-3-yliminomethyl)-5-methylphenol, 2-[(2-imidazol-4-yl)ethyliminomethyl]-5-methylphenol, 2-[(2-indol-3-yl-ethyl)iminomethyl]-5-methylphenol and 2-[2-(4-hydroxyphenyl)ethyliminomethyl]-5-methylphenol, all of which contain a biological directing functional group on the imine moiety, were investigated via crystallographic and DFT structural studies. Synthesis, in vitro cell testing and photoluminescence are reported indicating specific quantum yields and the respective suitability for radiopharmaceutical development.